Hero’s journey and archetypes found in Gaiman’s American Gods and Cline’s Ready Player One - Mohamed Roslan, Syed Mikhail (2020)
Mythology has been a subject matter that has been around since yesteryears with great influence on the progression of mankind. The topic of mythology has been assessed extensively in a range of fields based on several established theories and concepts. As initiated by Carl Jung, archetypes are ‘unconscious content’ reshaped by becoming conscious and by being perceived. Campbell applied archetypes to assess myths across the world, in which the findings are documented in his book entitled The Hero with a Thousand Faces. As such, a hero’s journey contains archetypes that form the whole journey. That being mentioned, this study assessed American Gods by Neil Gaiman and Ready Player One by Ernest Cline, as the subjects of analysis. This study assessed the representation of selected archetypes in and the impact of each archetype on the two stories. This study applied the archetypes defined by Jung and Campbell, to determine if the archetypes found in the selected novels are in accordance with the Hero’s Journey outlined by Campbell. The four archetypes assessed in this thesis are the Hero (protagonist), the Shadow (antagonist), the Lover, and the Sage. As a result, the influence exerted by the four identified archetypes varies in both novels. The Hero archetype is viewed as the main focus of a story, but American Gods is unique in the sense that it is due to the Shadow archetype that the Hero archetype perseveres. In Ready Player One, it follows a normal, stereotypical storyline, and yet both these stories follow the Hero’s Journey. It is noted that archetypes are not always portrayed the same as their influence differs. Archetypes may change their category but they retain their particular function at that particular time to focus on that particular moment. Thus, we are in the midst of a paradigm shift as archetypes evolve from their original moulds. All the four archetypes are strongly present in the stories and it can be concluded that both novels employ the Hero’s Journey in their narratives, despite this contemporary era. The stories resonate of myth- like elements and archetypal characters. To sum, archetypes are still important and valid as far as contemporary fictions are concerned.